IMPACT OF STUDENTS’ MOTIVATION TOWARDS ACADEMIC PERFORMANCE AT HIGHER SECONDARY LEVEL IN TEHSIL KAMALIA - Ruqyya Kousar; Shahnila Tubbsam; Umar Farooq; Muhammad Asghar (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of the study was to examine how motivation affects students' academic performance and how it enhances their personalities. The research area of study is Govt. colleges of tehsil Kamalia. There are 4 Govt. colleges which are Govt.PST Post Graduate College Kamalia, Govt. college of Technology Kamalia, Govt. College of Commerce Kamalia and Govt. Associate College (W) Kamalia. Total strength of higher secondary students of these colleges is 2905. Sample size of 184 students is determined out of 2905 students by using online software www.surveysystem.com. Respondents were selected from each college through proportionate sampling technique. A validated questionnaire was prepared. Statistical Package for Social Sciences (SPSS) is used to analyses data once it had been collected. Descriptive statistical analysis is used to determine mean values, percentages, standard deviations, weighted scores and rank orders. The results of the study shows that majority (64.9%) of the students are agreed that motivation is occurred from both ways intrinsically and extrinsically. Majority (36.41%) of the respondents are strongly agreed that teachers play a role of an observer. Most (38.59 %) of the respondents are agreed that teachers role as learner. Majority (41.30%) students achieve desire goal due to motivation. (44.02%) of respondents were strongly agree that productive learning enhanced due to motivation. Mostly (40.76 %) of the respondents are strongly agreed that class position improved. More than half (51.09 %) of respondents were agreed that mind mapping 0f students due to motivation which cause enhancement in academic achievements. Less than half (44.02%) of the respondents are strongly agreed that self- management skills improve. Most (42.39 %) of respondents agreed that decision making power of a person increased due to motivation. More than (53.26 %) respondents agreed that they actively attend the class. Less than half (46.74 %) of respondents enjoy the work and activities due to encouragement and praise receive from teachers. Majority (48.37%) of respondents felt confident about the content in a course. Class size should minimize for better academic achievements. Teachers should encourage the students. Monthly and weekly tests should be necessary for academic achievements of students; therefore tests should be conducted to improve the performance of students.